Pyschodermatology: a trip through history - Katlein Franca; Anna Chacon; Jennifer Ledon; Jessica Savas; Keyvan Nouri (Sociedade Brasileira de Dermatologia, 2013)
The interaction between the mind and diseases of the skin has been the study focus for many researchers worldwide. The field of Psychodermatology, or Psychocutaneous Medicine, is the result of the merging of two major medical specialties, psychiatry and dermatology. Although the history of Psychodermatology is rather old and interesting, the field has only recently gained popularity. Since ancient times, philosophers, surgeons, dermatologists and psychiatrists have reported the presence of psychocutaneous diseases in various scenarios. In this article, the authors describe curious and remarkable facts in the history of Psychodermatology.